2005
DOI: 10.1152/ajpheart.01162.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid-mediated augmentation of cardiomyocyte lipoprotein lipase involves actin cytoskeleton reorganization

Abstract: (J Mol Cell Cardiol 37: 931-938, 2004). Given that the actin cytoskeleton has been implicated in regulating cardiomyocyte LPL, we examined whether LPL secretion after LPA involves actin cytoskeleton reassembly. Incubation of myocytes with LPA (1-100 nM) increased basal and heparin-releasable LPL (HR-LPL), an effect that was independent of shifts in LPL mRNA. The influence of LPA on myocyte LPL was reflected at the coronary lumen, with substantial increases of the enzyme at this location. Incubation of myocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…In this setting, actin monomers are released from the phosphorylated HSP25 to self-associate to form fibrillar actin. We (34) and others (15) have reported actin cytoskeleton reorganization within the myocyte as an important means by which LPL is secreted onto plasma membrane HSPG binding sites. Since the increase in luminal LPL activity at 2 and 4 h after DEX corresponded to an enlargement in the F-actin/G-actin ratio, our data suggest that AMPK and p38 MAPK, through their control of HSP25 and the actin cytoskeleton act in unison to facilitate LPL translocation to the myocyte cell surface and ultimately to the coronary lumen.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this setting, actin monomers are released from the phosphorylated HSP25 to self-associate to form fibrillar actin. We (34) and others (15) have reported actin cytoskeleton reorganization within the myocyte as an important means by which LPL is secreted onto plasma membrane HSPG binding sites. Since the increase in luminal LPL activity at 2 and 4 h after DEX corresponded to an enlargement in the F-actin/G-actin ratio, our data suggest that AMPK and p38 MAPK, through their control of HSP25 and the actin cytoskeleton act in unison to facilitate LPL translocation to the myocyte cell surface and ultimately to the coronary lumen.…”
Section: Discussionmentioning
confidence: 84%
“…LPL at the coronary lumen is acquired from underlying cardiomyocytes. In these cells, following its synthesis, LPL is transported onto cell surface HSPG binding sites (34). To directly examine the effects of DEX on myocyte LPL, control cardiomyocytes were incubated with DEX for varying times.…”
Section: General Characteristics Of the Experimental Animalsmentioning
confidence: 99%
“…The unbound fluorescent probe was rinsed with PBS buffer and slides visualized and photographed with a Leica fluorescent microscope (Wetzlar, Postfach, Germany). The effects of AICAR in myocytes were also determined in the presence or absence of 1 mol/l CTD (an actin polymerization inhibitor) (30). Silencing of p38 MAPK by small interfering RNA.…”
Section: Methodsmentioning
confidence: 99%
“…At the endothelial cell, we reported that TG 16 and lipoprotein breakdown products like lysophosphatidylcholine, 17 likely through their release of heparanase, enabled myocyte HSPG cleavage and transfer of LPL toward the coronary lumen. Within the myocyte, recruitment of LPL to the cell surface was controlled by stress kinases like AMPK and p38 MAPK, which allowed for actin cytoskeleton polymerization and provision of a network that facilitated LPL movement.…”
mentioning
confidence: 96%